The Strategy of Boosting the Immune System Under the COVID-19 Pandemic - Alagawany, Mahmoud; Attia, Youssef A.; Farag, Mayada R.; Elnesr, Shaaban S.; Nagadi, Sameer A.; Shafi, Manal E.; Khafaga, Asmaa F.; Ohran, Husein; Alaqil, Abdulaziz A.; Abd El-Hack, Mohamed E. (Frontiers in Veterinary Science, 2021)
The novel coronavirus (SARS-CoV-2) infection (COVID-19) has raised considerable concern on the entire planet. On March 11, 2020, COVID-19 was categorized by the World Health Organization (WHO) as a pandemic infection, and by March 18, 2020, it has spread to 146 countries. The first internal defense line against numerous diseases is personalized immunity. Although it cannot be claimed that the personalized nutrition will have an immediate impact on a global pandemic, as the nutritional interventions required long time to induce beneficial outcomes on immunity development, the nutritional strategies still able to clarify and have a beneficial influence on the interplay between physiology and diet, which could make a positive contribution to the condition in the next period. As such, a specific goal for every practitioner is to evaluate different tests to perceive the status of the patient, such as markers of inflammation, insulin regulation, and nutrient status, and to detect possible imbalances or deficiencies. During the process of disease development, the supplementation and addition of different nutrients can influence the viral replication, but also the cellular mechanisms. It is essential to understand that every patient has its individual needs. Even though many nutrients and drugs have beneficial effects on the immune response and can prevent or ameliorate viral infections, it is essential to detect at what stage in COVID-19 progression the patient is at the moment and decide what kind of nutrition intervention is necessary. Furthermore, understanding the pathogenesis of coronavirus infection is critical to make proper recommendations.